2015
DOI: 10.1378/chest.14-0976
|View full text |Cite
|
Sign up to set email alerts
|

CT Scan Findings of Probable Usual Interstitial Pneumonitis Have a High Predictive Value for Histologic Usual Interstitial Pneumonitis

Abstract: BACKGROUND: Th e current usual interstitial pneumonitis (UIP)/idiopathic pulmonary fi brosis CT scan classifi cation system excludes probable UIP as a diagnostic category. We sought to determine the predictive eff ect of probable UIP on CT scan on histology and the eff ect of the promoter polymorphism in MUC5B (rs35705950) on histologic and CT scan UIP diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 37 publications
5
87
0
11
Order By: Relevance
“…This case underscores findings in the literature indicating that characteristic HRCT features are not present in ∼30-40% of IPF patients and that lung biopsy may be needed to confirm diagnosis [27]. There is a growing body of evidence suggesting that subjects with probable IPF, accounting for ∼16% of cases, are likely to have UIP pattern on lung biopsy (82%) [28,29]. Interestingly, FELL et al [30] showed that in patients aged over 65 years with reticular abnormalities but no honeycombing, as described in the case above, the diagnostic likelihood of IPF exceeded 95%.…”
Section: Discussionsupporting
confidence: 54%
“…This case underscores findings in the literature indicating that characteristic HRCT features are not present in ∼30-40% of IPF patients and that lung biopsy may be needed to confirm diagnosis [27]. There is a growing body of evidence suggesting that subjects with probable IPF, accounting for ∼16% of cases, are likely to have UIP pattern on lung biopsy (82%) [28,29]. Interestingly, FELL et al [30] showed that in patients aged over 65 years with reticular abnormalities but no honeycombing, as described in the case above, the diagnostic likelihood of IPF exceeded 95%.…”
Section: Discussionsupporting
confidence: 54%
“…Test characteristics included sensitivity, specificity, PPV, negative predictive value, area under the receiver-operator curve and positive likelihood ratios (LR+). To further demonstrate the effect of differing population prevalence rates (ie, differing pretest probabilities) of histopathological UIP on post-test probabilities, histopathological UIP prevalence rates were varied across a hypothetical range 10 12. Several sensitivity analyses were performed: including cases with possible UIP/unclassifiable PF on histopathology as ‘positive’ outcome (ie, as equivalent to definite/probable UIP cases); using the clinical diagnosis of IPF rather than histopathological UIP as the outcome; including patients with diagnoses of a defined connective tissue disease (CTD) prior to biopsy; and using individual radiologist interpretations of HRCT pattern rather than consensus pattern.…”
Section: Methodsmentioning
confidence: 99%
“…In a prior study, we reported on 201 of the 1,764 subjects included in the current study. 16 The prior report only included subjects with pathologic correlation; the current study expands on this by having a much larger subject number and includes new evaluation of the CT imaging pattern of pulmonary fibrosis relative to the MUC5B promoter site polymorphism. Of the 1,764 subjects, 1,491 had evidence of pulmonary fibrosis on chest CT scans and were included in our study.…”
Section: Study Populationmentioning
confidence: 99%
“…Confidence of diagnosis specific to UIP was scored as inconsistent with UIP, indeterminate UIP, probable UIP, or UIP depending on the radiologists' opinion of the likelihood of the diagnosis based on imaging findings (Figs 1-4). [16][17][18][19] A UIP pattern was defined as basilar and peripheral preponderant fibrosis with honeycombing and absence of features to suggest another alternative diagnosis. Probable UIP was defined as basilar and peripheral preponderant fibrosis with little or no honeycombing and absence of features to suggest another alternative diagnosis.…”
Section: Ct Imaging Evaluationmentioning
confidence: 99%